2016
DOI: 10.1037/xge0000195
|View full text |Cite
|
Sign up to set email alerts
|

Strong genetic overlap between executive functions and intelligence.

Abstract: Executive functions (EFs) are cognitive processes that control, monitor, and coordinate more basic cognitive processes. EFs play instrumental roles in models of complex reasoning, learning, and decision-making, and individual differences in EFs have been consistently linked with individual differences in intelligence. By middle childhood, genetic factors account for a moderate proportion of the variance in intelligence, and these effects increase in magnitude through adolescence. Genetic influences on EFs are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
73
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 102 publications
13
73
0
1
Order By: Relevance
“…Our results fall in line with the previous findings of Engelhardt et al. (), who used psychometric testing to show that a strong genetic component exists within executive functions.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results fall in line with the previous findings of Engelhardt et al. (), who used psychometric testing to show that a strong genetic component exists within executive functions.…”
Section: Discussionsupporting
confidence: 93%
“…While previous studies made the simple assumption that observed heritability in response time is attributable solely to heritability in the speed of mental processing (Beaujean, 2005;Finkel & Pedersen, 2004;Kochunov et al, 2016;Luciano et al, 2001;Ogata et al, 2014;Posthuma et al, 2002;Vernon, 1989), we found greater genetic contribution to response caution than to underlying cognitive speed within the memory task assessed. Our results fall in line with the previous findings of Engelhardt et al (2016), who used psychometric testing to show that a strong genetic component exists within executive functions. Previous twin-based studies have investigated the heritability of decision-related processes, such as processing speed, through psychometric tests, linear correlations, and structural equation models (Vernon, 1989).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…A hierarchical structure, which highlights both communalities 384 and differences between cognitive tests, has also been found to provide the most accurate characterization in 385 other domains of cognition, most notably executive functions. [39][40][41][42] Also consistent with what has been observed 386 for individual differences in executive functions, we found that genetic factors were largely shared across all 387 tests of spatial abilities. These results point to the existence of a common genetic network at the basis of 388 individual differences in spatial ability, therefore providing additional support for a unitary account of spatial 389 cognition.…”
Section: 325supporting
confidence: 84%